A Project Feasibility Study on Cocotiles - Bango, Emilio Hiadan Jr; Caisip, Jay Hilario; Maog, Moises; Pascual, Francisco (College of Engineering, 1996)
The project feasibility study sought to investigate whether the manufacture of Cocotiles (flooring tiles made from coconut shell and fiber) is viable by subjecting it to exhaustive evaluation consisting of five phases: market feasibility, technical feasibility, financial feasibility, social feasibility and organization & management study. The market feasibility began with quantitative analysis of demand-supply data to determine past and present industry behavior and future trends. It was determined that a market exists for coconut shell floor tiles, the potential consumers being NCR private houseowners and construction companies. Given the first year demand for flooring tiles is found to be 9.6%. A manifold marketing plan was formulated which proved that target demand is realizable. From the marketing phase, a five-year sales plan was drawn up, which formed the basis for the production program under the technical phase. The technical study brought to light the following. The primary manufacturing equipment is available for importation, while secondary equipment is available locally. Raw materials are available in sufficient quantities, at a fair price, and are of required specifications. The manpower needed as well as the proposed plant location are available locally. It was evaluated and determined that the plant would be best located at #6 Barangay Road, Barrio Yukos, Nagcarlan, Laguna. In short, it is technologically possible to produce Cocotiles in the required quantities. The financial phase analyzed the total project cost and the annual manufacturing expense of the company. It was determined that the total cost needed to start the project is P68 258 544.82 The needed capital to fund the project is realizable through equity investment and commercial loans. The primary source of funding will come from investors who will put up 60% of the needed initial funds or P40 955 126.89. The reset of the needed funding will come from a loan, which will amount to P27 303 417.93. The financial position of the company was measured through financial ratios, and sensitivity analysis was conducted on the relevant project factors. The Internal Rate of Return (IRR) was computed to be 23%, more than the 20% minimum attractive rate of return. It was also established that the payback period is 4 years. The first year net income is favorable, which amounts to P10 634 315.70. The social profitability phase established that the project?s realization would render numerous community and governmental benefits, while utilizing safe technology. The productive potential of local raw materials would be demonstrated, thus inspiring research on further applications. Finally, in the organizational and management phase, it was decided that the form of ownership would be of a corporation type. The production of Cocotiles is a large scale venture and it requires a huge capital investment. The plant direct labor force needed is 40 workers; the plant indirect labor force is 10, while the sales office is to be manned by a total of 5 employees. Therefore, the project is expected to generate 55 full time jobs.